Methamphetamine-Induced cardiomyopathy in young adult man: A case report. - Hernandez - Aguirre , U.G,.; Isais - Moreno, D.M.; Prieto-Lavin , C.M.,; Adonia - Machore , M.A. (Revista de Ciencias Médicas Torreón, 2026)
Methamphetamine-associated cardiomyopathy (MACM)causes structural and functional myocardial abnormalitiesthat can progress to advanced heart failure and evennecessitate heart transplantation. We present the case of a 23-year-old man with an eight-year history of methamphetamineuse and abuse who presented to the emergency departmentwith severe dyspnea on minimal exertion and lower-extremity edema. He denied any personal or family history ofcardiovascular disease. Urine toxicology screening waspositive for methamphetamines. Physical examinationrevealed advanced heart failure, classified as New YorkHeart Association (NYHA) functional class IV. He washospitalized for three days and treated with diuretics—primarily loop diuretics—showing clinical improvement.Rising methamphetamine use and its initiation at youngerages have contributed to the emergence of MACM in youngpatients. This underscores the importance of maintaining ahigh index of clinical suspicion in patients with a history ofuse, regardless of age. Early cardiological assessment allowsfor the detection of subclinical ventricular dysfunction andintervention prior to irreversible myocardial damage.We present and discuss the case of a young adult withdyspnea at rest secondary to severe dilated cardiomyopathyassociated with chronic methamphetamine use.